what you need to do is a two-step process:

step one: find the "change of basis matrix" P. to be explicit, the P we are going to use is the one that changes B-coordinates to standard coordinates.

since [1,0]_{B}= 1(2,0) + 0(1,1) = (2,0), we have:

which makes it clear P is of the form:

similarly, since [0,1]_{B}= (1,1), we have that:

so the overall procedure is this:

B-coordinate input ---> change to standard coordinates --->apply standard T (matrix A) ---> change back to B-coordinates.

to change back to B--coordinates, we need to use P^{-1}, which is:

step 2: find the desired matrix for T, which is:

.

let's verify that this actually works:

we know that T(x,y) = (x+2y,y).

writing (x,y) in B-coordinates, we get: (x,y) = x(1,0) + y(0,1) = x[1/2,0]_{B}+ y[-1/2,1]_{B}= [(x-y)/2,y]_{B}.

applying our [T]_{B}to [(x-y)/2,y]_{B}(to get [T(x,y)]_{B}), we obtain:

[T]_{B}([(x-y)/2,y]_{B}) = [(x-y)/2+y,y]_{B}= [(x+y)/2,y]_{B}.

changing this back to standard coordinates, we have:

[(x+y)/2,y]_{B}= ((x+y)/2)[1,0]_{B}+ y[0,1]_{B}= ((x+y)/2)(2,0) + y(1,1) = (x+y,0) + (y,y) = (x+2y,y) = T(x,y).